World Histories of Big Data Policing - Brendan McQuade (Journal of World-Systems Research, 2021)
Textbook presentations of U.S. policing name the present as new stage of professionalization: the homeland security era, where the application of “big data” promises “smarter” policing. Within this framework of gradual progress, liberal police scholarship has become the official criticism of big data policing to organize a project of liberal reform. Of course, this scholarship is being in written in the context of both militant social movements within the United States and the terminal decline of U.S. global hegemony. To clarify the stakes of this moment, this paper connects the Marxist anti-security perspective and anti-racist critiques of surveillance and big data policing from within the Black radical tradition. It argues that the emergence of big data policing is the latest development in on-going processes of pacification that have expanded, organized, and reproduced the colonial/modern world-system over the longue durée.  The paper extends and elaborates conceptualizations of hegemonic cycles in relation to work on the maturation of intelligence tradecraft, focusing on two interrelated developments: (1) two information revolutions that reorganized social relations and (2) the police-wars that shaped the rise and decline of the United States as a world hegemonic power. It concludes that big data policing is the latest outgrowth of the imperial epistemology that organized and continues animate the work of pacification and obscure the politics of anti-systemic struggle.